Testing Thymol-Based DES for the Elimination of 11 Textile Dyes from Water - Lorena Villar; Óscar Martínez-Rico; Andrés Asla; Ángeles Domínguez; Begoña González (Separations, 2022)
Textile industries release dangerous wastewater that contain dyes into the environment. Due to their toxic, carcinogenic and mutagenic nature, they must be removed before the discharge. Liquid–liquid extraction has proven to be an efficient method for the removal of these dyes. As extractants, deep eutectic solvents (DESs) have shown excellent results in recent years, as well as presenting several green properties. Therefore, four different hydrophobic DESs based on natural components were prepared thymol:decanoic acid (T:D (1:1)), thymol:DL-menthol (T:M (1:1)), thymol:DL-menthol (T:M (1:2)) and thymol:coumarin (T:C (2:1)) for the extraction of Malachite Green (MG), Brilliant Blue G (BBG), Acid Yellow 73 (AY73), Reactive Red 29 (RR29), Acid Blue 113 (AB113), Reactive Black 5 (RB5), Remazol Brilliant Blue (RBB), Direct Yellow 27 (DY27), Acid Blue 80 (AB80), Direct Blue 15 (DB15) and Acid Violet 43 (AV43) dyes from water. The operational parameters of the liquid–liquid extraction were selected in order to save time and materials, resulting in 30 min of stirring, 15 min of centrifugation and an aqueous:organic ratio of 5:1. In these conditions, the highest values of extraction obtained were 99% for MG, 89% for BBG and 94% for AY73. Based on these results, the influence of the aqueous:organic phase ratio and the number of necessary stages to achieve water decolorization was studied.